A Rare Case of Asymptomatic Postmenopausal Tubercular Endometritis in Italy - Caterina Pizzicaroli; Giovanni Larciprete (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2016)
Introduction: Tuberculosis affects about a third of world population. Genitourinary tuberculosis is one of the most common manifestations of extra pulmonary tuberculosis. Postmenopausal tubercular endometritis is an uncommon condition that usually occurs with abnormal vaginal bleeding.  Aim: The aim of the paper is to report a rare case of asymptomatic postmenopausal tubercular endometritis.  Case report: Trans-abdominal and trans-vaginal ultrasound performed in a 59 years-old Romanian asymptomatic woman showed a huge hypo-echoic area centrally located in the uterine shape and a severe endometrial hypo-echoic thickness ( > 2 cm). Color Doppler did not detect any vascularity into this area. Magnetic Resonance Imaging (MRI) of the lower abdomen confirmed the severe endometrial thickness. The histopathological diagnosis obtained by biopsy during hysteroscopy documented tubercular endometritis. The patient started a medical treatment for tuberculosis. Forty days later a control ultrasound showed the fluidization of the caseous material in the uterine cavity.  Discussion: The main localizations of genitourinary tuberculosis are primarily the fallopian tubes, then it spreads towards endometrium, cervix, vagina and ovaries. In post-menopausal age patients with tubercular endometritis usually present with a story of vaginal bleeding; however, patients may be asymptomatic or they may present aspecific symptoms. This usually leads to a delay in diagnosis and therapeutical interventions.  Conclusions: Tubercular endometritis is a severe disease that may affect both pre- and postmenopausal woman. Symptoms could be absent or aspecific. Diagnosis is not simple and it often needs laparoscopy, laparotomy or hysteroscopy. Histology is needful for the correct diagnosis. A standard medical anti-tubercular therapy of 6 months is often sufficient to obtain a complete therapeutical response. In some selected cases surgery may be necessary. In our paper, an asymptomatic woman in post-menopausal age, affected by endometrial tuberculosis showed clinical response after a standard antitubercular medical therapy.